Scaling of bony canals for encephalic vessels in euarchontans: Implications for the role of the vertebral artery and brain metabolism. Issue 114 (January 2018) - Boyer, Doug M.; Harrington, Arianna R.
Abstract: Supplying the central nervous system with oxygen and glucose for metabolic activities is a critical function for all animals at physiologic, anatomical, and behavioral levels. A relatively proximate challenge to nourishing the brain is maintaining adequate blood flow. Euarchontans (primates, dermopterans and treeshrews) display a diversity of solutions to this challenge. Although the vertebral artery is a major encephalic vessel, previous research has questioned its importance for irrigating the cerebrum. This presents a puzzling scenario for certain strepsirrhine primates (non-cheirogaleid lemuriforms) that have reduced promontorial branches of the internal carotid artery and no apparent alternative encephalic vascular route except for the vertebral artery. Here, we present results of phylogenetic comparative analyses of data on the cross-sectional area of bony canals that transmit the vertebral artery (transverse foramina). These results show that, across primates (and within major primate subgroups), variation in the transverse foramina helps significantly to explain variation in forebrain mass even when variation in promontorial canal cross-sectional areas are also considered. Furthermore, non-cheirogaleid lemuriforms have larger transverse foramina for their endocranial volume than other euarchontans, suggesting that the vertebral arteries compensate for reduced promontorial artery size. We also find that, among internal carotid-reliant euarchontans, species that are more encephalized tend to have a promontorial canal that is larger relative to the transverse foramina. Tentatively, we consider the correlation between arterial canal diameters (as a proxy for blood flow) and brain metabolic demands. The results of this analysis imply that human investment in brain metabolism (∼27% of basal metabolic rate) may not be exceptional among euarchontans.